# 3(5x-4)=8x+2

### 8 Answers | Add Yours

We can say that this problem is looking for the value of x.

3(5x - 4) = 8x + 2

The first thing to do is to simplify the equation by removing the parenthesis. We can do that if we multiply 3 with (5x - 4);

15x - 12 = 8x + 2

Next, we should combine like terms.

----->add 12 on both sides

15x - 12 + 12 = 8x + 2 + 12

15x = 8x + 14

----->subtract 8x on both sides

15x - 8x = 8x - 8x + 14

7x = 14

To solve for x, we divide both sides by 7.

7x = 14

--- ---

7 7

**therefore the answer is x = 2.**

3(5x-4)=8x+2

7x=14

x=2

Solve for x

3(5x-4)=8x+2

Distribute

15x-12=8x+2

Move the variables to one side

15x-8x=2+12

7x=14

x=2

3 ( 5x - 4 ) = 8x + 2

First distribute the equation

By distributing the equation , your equation should look like

**15x - 12 = 8x + 2 **now subtract 8x on both sides in order to get the " x " alone

By subtracting, your equation should look like

**7x - 12 = 2** Add 12 on both sides

By adding, your equation should look like

**7x = 14 **Divide both sides by 7

By dividing your equation should look like

**x =2 **which is your answer

3(5x-4)=8x+2

15x-12=8x+2

7x-12=2

7x=14

x=2

3(5x-4)=8x+2 distribute the 3

15x-12=8x+2 combine like terms

15x-8x=2+12

7x=14 now divide by 7

x=2

3(5x-4)=8x+2

15x-12=8x+2

7x=14

x=2

to prove **3(5x-4)=8x+2**

first we have to find the value of x

multiply 3 with 5x and -4

we get 15x-12

15x-12=8x+2

by L.H.S. n R.H.S.

15x-12+12=8x+2+12

15x-8x=8x+14-8x

7x=14

7x/7=14/7

x=2

now,

put 2 in place of x

3{(5*2)-4}=(8*2)+2

3{10-4}=16+2

3*6=18

**18=18**

*hence proved*